Food and cutaneous pathology. - Meneghini, C.L.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
Aliment is any organic or inorganic substance which is scissible in simpler elements utilizable by the organism for the different nutritive and metabolic functions. Essential aliments of an organism other than water are the proteins (scissible in polypeptides, peptides and aminoacids), the glucides, and the lipids. These last two elements furnish the most consistent amount of calories (a calorie is the amount of heat necessary to increase from 14.5°C to 15.5°C the temperature of 1g of water at the pressure of 1 atmosphere). (...).